PENGARUH VARIASI KOMPOSISI KOMPOSIT RESIN EPOXY/SERAT GLASS DAN SERAT DAUN NANAS TERHADAP KETANGGUHAN - Hendriwan Fahmi; Nur Arifin (Jurnal Teknik Mesin, 2014)
Fiber of pineapple leaf as one of the natural fiber which is very abundant availability at this time, but is no longer used and disposed of as waste. Though pineapple leaf fiber can be used as a natural alternative to fiber composite materials. The purpose of this study was to determine the effect of variations in the composition of the composite epoxy / glass fiber and pineapple leaf fiber on impact toughness, and also can utilize waste pineapple leaf fibers. Pineapple leaf fiber combined with glass fibers in order to obtain optimum strength and toughness. Variation of weight percent composition of the composite is 90:10, 80:20, 70:30, 60:40. The process of manufacture of the specimen is done manually and stirring pineapple leaf fiber and glass fiber with resin done evenly and constantly. Pouring resin into the mold do without the absence of pressure. Of the results impact test be obtained impact energy and price of impact average for the composite with composition 90:10 = 0.12 J for impact energy and for price impact 0.003 J/mm2 , 80:20 = 0.0013 J for impact energy and price impact 0.0033 J/mm2 , 70:30 = 0.32 J for impact energy and price impact of 0.008 J/mm2 , 60:40 = 0.31 J for impact energy and price impact 0.0077. Toughness is highest obtained on the 70:30 composition. From the test results it can be concluded that the natural fiber – reinforced composites and glass fiber can improve the toughness in the shock loads